STRATEGI PENYULUH AGAMA ISLAM DALAM UPAYA MEMINIMALISIR TERJADINYA PERCERAIAN DI MASYARAKAT - Wasik, Abdul; Yakin, Ainul; Rizal FR, Muhammad; Ahmad, Malik Abdillah; romadoni, Ahmad (International Conference on Humanity Education and Society (ICHES), 2024)
Abstract This study raises the subject of "Islamic Extension Strategy in an Effort to Minimize the Occurrence of Divorce in Society with sub-problems behind the occurrence of divorce? duties and functions of KUA extension workers? Strategies used in an effort to minimize the occurrence of divorce in the community. The purpose of this study is to provide the development of science on the background of divorce, knowing the duties and functions of Islamic Extension Counselors, To find out the strategies used by Islamic Extension Counselors in an effort to minimize the occurrence of divorce in the community. The research approach that researchers use is field research using a qualitative approach. The results showed that the strategy used by extension workers was in the form of a suscatin program, conducting marriage counseling, conducting advice before and after the marriage contract. The implication of this study is, For KUA institutions are expected to further develop the function of extension workers in an effort to prevent divorce, For Islamic extension workers, they should be more active in approaching the community for the smooth running of the activities carried out For the community, it is expected to actively participate in the activities of the scientific assembly through meetings and direct communication by not prioritizing social media.